Constitutional translocation breakpoint mapping by genome-wide paired-end sequencing identifies HACE1 as a putative Wilms tumour susceptibility gene. Issue 5 (30th November 2009) - Slade, I; Stephens, P; Douglas, J; Barker, K; Stebbings, L; Abbaszadeh, F; Pritchard-Jones, K; ,; Cole, R; Pizer, B; Stiller, C; Vujanic, G; et al.
Abstract : Background: Localisation of the breakpoints of chromosomal translocations has aided the discovery of several disease genes but has traditionally required laborious investigation of chromosomes by fluorescent in situ hybridisation approaches. Here, a strategy that utilises genome-wide paired-end massively parallel DNA sequencing to rapidly map translocation breakpoints is reported. This method was used to fine map a de novo t(5;6)(q21;q21) translocation in a child with bilateral, young-onset Wilms tumour. Methods and results: Genome-wide paired-end sequencing was performed for approximately 6 million randomly generated ∼3 kb fragments from constitutional DNA containing the translocation, and six fragments in which one end mapped to chromosome 5 and the other to chromosome 6 were identified. This mapped the translocation breakpoints to within 1.7 kb. Then, PCR assays that amplified across the rearrangement junction were designed to characterise the breakpoints at sequence-level resolution. The 6q21 breakpoint transects and truncates HACE1, an E3 ubiquitin-protein ligase that has been implicated as a somatically inactivated target in Wilms tumourigenesis. To evaluate the contribution of HACE1 to Wilms tumour predisposition, the gene was mutationally screened in 450 individuals with Wilms tumour. One child with unilateral Wilms tumour and a truncating HACE1 mutation was identified. Conclusions: These data indicate that constitutional disruption of HACE1 likely predisposes to Wilms tumour. However, HACE1 mutations are rare and therefore can only make a small contribution to Wilms tumour incidence. More broadly, this study demonstrates the utility of genome-wide paired-end sequencing in the delineation of apparently balanced chromosomal translocations, for which it is likely to become the method of choice.